SISTEM PENDIDIKAN ISLAM DI ANDALUSIA DAN KONTRIBUSINYA TERHADAP PENDIDIKAN ISLAM MASA SEKARANG - Rahma Dona; Salmi Wati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The development of Islamic education is always related to the periodization of Islamic history itself, one of which is education during the Umayyad Andalusian Dynasty. The purpose of this study is to find out; the history of the Umayyad Andalusian Dynasty, the education system of the Umayyad Andalusian Dynasty and the contribution of education in Andalusia to Islamic education today. This study uses a qualitative approach with a library research method through the collection of primary and secondary data from various information related to the history of the Umayyad Andalusian Dynasty, its education system. The results of this study indicate that Islam entered Andalusia in 711 AD under the leadership of Commander Thariq bin Ziyad. Islamic education has succeeded in giving birth to brilliant ideas in almost various disciplines. In addition, the progress of Andalusian culture can contribute to the development of better governance in the aspects of education, educational opportunities, and all efforts to develop to advance education, both general and Islamic education. The Islamic education system in Andalusia is an important main aspect in the history of Islamic education. His contribution to the development of science, integrative approaches, and teaching methods are still relevant and applied in Islamic education today. The combination of religious and general knowledge inherited from Andalusia inspires the modern education system today to continue to develop scientific traditions that include implementing general education without abandoning Islamic values.